Pore Structure and Permeability of Cementitious Materials Containing a Carboxylic Acid Type Hydrophobic Agent - Zhang, Hao; Zhou, Ying; Mu, Song; Cai, Jingshun; Hong, Jinxiang; Liu, Jianzhong; Zhao, Yongqiang (Frontiers in Materials, 2022)
Integral hydrophobic treatment is the most effective method to prolong service life of concrete by resisting the transport of water containing aggressive ions. The hydrophobicity phenomenon of cementitious materials with carboxylic acid type admixture has been presented and the experimental studies including water adsorption, amount of hydration products and pore system are conducted to reveal the hydrophobicity mechanism. It is reported that cementitious materials containing hydrophobic admixture presents excellent water resistance ability, the experimental results of nitrogen adsorption isotherm show that carboxylic acid type admixture addition increases pore volume and surface area of cement pastes. In addition, fractal geometry theory is applied to reveal the relation between the pore structure and the permeability coefficient of cement pastes with hydrophobic agent. In conclusion, the high tortuosity fractal dimension and the hydrophobicity of pores surface result in the water resistance when cementitious system is mixed with new type hydrophobic admixture.